Integral Type F-Contractions in Partial Metric Spaces - Vildan Ozturk (Journal of Function Spaces)
Partial metric spaces were introduced as a generalization of usual metric spaces where the self-distance for any point need not be equal to zero. In this work, we defined generalized integral type F-contractions and proved common fixed point theorems for four mappings satisfying this type (Branciari type) of contractions in partial metric spaces.